Exploring the Transition to Eudaimonic Tourism: A Case Study of Bali - Djisman Simandjuntak; Alvin Desfiandi; Erica Lukas; Isti Setiawati; Nakita Sabrina; Stanley Makalew (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2019)
Growing population with rising income, advances in information and transportation technologies, preventive medicine, moderated nationalism that translate into less restrictive border measures against people flows have combined to fuel a durable progressive growth in tourism, domestic and international. As tourism grows, carrying capacity is stretched or even overstretched in some places and industries. The overcrowding of a destination in the latter’s life cycle is familiar to popular tourist sites. Energy consumption, CO2 emission, non-degradable and toxic wastes, biodiversity loss and loss of cultural diversity add to the downside of growing tourism. We doubt the inclusivity and sustainability of the current dominant design of tourism in developing economies such as Indonesia. A shift toward more eudaimonic tourism is needed. The innovative elements of eudaimonia include geographical treasure, biodiversity, and local deep culture. Indonesia is well endowed with peculiar geographical resources which in turn result in rich biodiversity. A long history of migration has also accumulated Indonesia’s cultural diversity. Bali offers an imperfect road to eudaimonic tourism as will be discussed as evidence that the shift away from exclusive and unsustainable tourism to a more inclusive and sustainable one is a realistic option. Keywords: eudaimonic; tourism; inclusivity; sustainability